(untitled) (Annals of Medical Research, 2021)
Aim: In this study we aimed to compare the retrospective results of the success rates in children with congenital nasolacrimal duct obstruction undergoing monocanalicular and bicanalicular silicone tube intubation. Materials and Methods: Bicanalicular (Group 1) and monocanalicular (Group 2) silicone tube intubation was performed in 48 eyes of 42 patients using the Ritleng method. Sixteen of the patients were boys and 26 were girls. Bicanalicular silicone tube intubation was performed in 26 eyes of 22 patients, and monocanalicular silicone tube intubation was performed in 22 eyes of 20 patients. Results: The mean age of patients was 5.68±1.83 years (2-9 years) in the first group, and 5.05±1.76 years (3-9 years) in the second group. The period of leaving the silicone tube was 3.61±1.38 months (1-6 months) in the first group, and 3.18±1.00 months (1-6 months) in the second group. The mean follow up period of the patients was found to be 11.8 months (6-36 months) in the bicanalicular group and 14.0 months (6-36 months) in the monocanalicular group.The success rate was 92.30% (22 of 26 eyes) in the first group and 95.45% (21 of 22 eyes) in the second group. In the first group, 2 patient’s bicanalicular tube was removed spontaneously 2 months ago, 2 patients were performed dacryocystorhinostomy, 1 patient developed pyogenic granuloma and laceration occurred in the lower canaliculus of 1 patient. In the second group, the tubes of 2 patients were removed spontaneously 2 months ago and silicone tube intubation was performed again with the same method. In this group, 1 patient was then performed dacryocystorhinostomy and 1 patient developed conjunctivitis. There were no corneal or conjunctival complications in either group. Conclusion: There was no statistically significant difference in success rates between the groups (p>0.05).